Development and experimental study on a pilot-scale feed pellet mill - Peng, Fei; Fang, Fang; Huang, Zhigang (International Journal of Agricultural and Biological Engineering, 2020)
Pilot-scale pellet mill has many advantages and great potential application prospect. In this work, a structure of pilot-scale pellet mill was designed and the effects of moisture content (12%-20% w.b.), temperature (55°C-95°C) and ring die speed (160-320 r/min) on the production and physical properties (pellet durability, bulk density and hardness) of the produced feed pellets were determined and analyzed. The results showed that pellet durability ranged from 90.47% to 96.92%, bulk density 537.4 kg/m3 to 62.2 kg/m3, hardness 5.26 kg to 9.65 kg and production 26.51 kg/h to 42.81 kg/h. Pellet durability was found to increase with the increase of temperature and moisture content, but to decrease with the increase of ring die speed. Bulk density showed a monotonic increase with temperature and ring die speed. Hardness increased with the increase of temperature, but exhibited a first ascending and then descending trends with the increase of moisture content. It also indicted that high ring die speed favored production. Due to its fast and cheap production in a suitable scale, the designed pilot scale pellet mill prototype and the comprehensive research would contribute to the production of feed pellets in various processing conditions with different feed formulas, like additive selection and so on, in order to meet diversified demands. Keywords: feed, pilot-scale, pellet mill, experimental study, ring die speed DOI: 10.25165/j.ijabe.20201306.5826 Citation: Peng F, Fang F, Huang Z G. Development and experimental study on a pilot-scale feed pellet mill. Int J Agric & Biol Eng, 2020; 13(6): 201–206.